Penerapan Metode Blended Learning Berbasis Aplikasi seTARA Daring untuk Meningkatkan Minat Belajar Peserta Didik Pasca Pandemi di Program Kesetaraan Paket C PKBM Budi Utama Surabaya - Rahayu Sri Lestari; Wiwin Yulianingsih (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The purpose of this study is to determine the application of the seTARA Daring application-based blended learning method and determine the level of interest in learning students of the post-pandemic Package C equivalence program. This study uses a descriptive qualitative method with a type of field research. Data collection using observation techniques, interviews, field notes and documentation. The data analysis is carried out by collecting data, reducing data, presenting data and drawing conclusions.The results of the research obtained show that the application of the seTARA Daring application-based blended learning method after the pandemic can create learning activities that are more flexible, effective and efficient in the use of time. The interest in learning students increases as seen from the enthusiasm and activeness in participating in learning. In the process of applying the application-based blended learning method seTARA Daring, there are supporting and inhibiting factors that affect the interest in learning students.